2008
DOI: 10.1590/s1415-43662008000400004
|View full text |Cite
|
Sign up to set email alerts
|

Índices de crescimento da cana-de-açúcar irrigada e de sequeiro no Estado da Paraíba

Abstract: O experimento foi montado na Fazenda Capim II, situada na Cidade de Capim, PB, com o objetivo de se avaliar os índices de crescimento da parte aérea e do sistema radicular da variedade SP 79 1011 de cana-de-açúcar (Saccharum officinarum L.), em regime irrigado e de sequeiro. O delineamento estatístico foi o de blocos casualizados, em esquema fatorial 2 x 6, com três repetições, sendo realizadas seis amostragens de plantas e analisados os componentes da parte aérea e do sistema radicular. A taxa máxima de acúmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1
47

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 8 publications
3
24
1
47
Order By: Relevance
“…On that same layer, T50% treatment had the lowest mean observed, concentrating 76.43% of total roots (Figure 4). The absence of irrigation with treatment TWI stimulated deep root growth and further development side, especially in the layer from 0.00 to 0.20 m, which ensured the concentration of 80% of the roots depth of 0.00 -0.40 m. Results of cumulative percentage of roots occurred in all treatments are according to Farias et al (2008), in stating that in general, up to 76% of the roots of sugarcane are the first 0.45 m of soil depth. These authors evaluated the development of the root system of sugar cane irrigated and cultivated without irrigation after 280 days of implantation of the experiment, and observed that the sugar cane grown without irrigation in 80% of the dry weight of roots in the first 0, 60 m depth of soil, and when irrigated, that figure increased to 90%.…”
Section: Effective Root Depthmentioning
confidence: 89%
See 2 more Smart Citations
“…On that same layer, T50% treatment had the lowest mean observed, concentrating 76.43% of total roots (Figure 4). The absence of irrigation with treatment TWI stimulated deep root growth and further development side, especially in the layer from 0.00 to 0.20 m, which ensured the concentration of 80% of the roots depth of 0.00 -0.40 m. Results of cumulative percentage of roots occurred in all treatments are according to Farias et al (2008), in stating that in general, up to 76% of the roots of sugarcane are the first 0.45 m of soil depth. These authors evaluated the development of the root system of sugar cane irrigated and cultivated without irrigation after 280 days of implantation of the experiment, and observed that the sugar cane grown without irrigation in 80% of the dry weight of roots in the first 0, 60 m depth of soil, and when irrigated, that figure increased to 90%.…”
Section: Effective Root Depthmentioning
confidence: 89%
“…This statement is reinforced by Farias et al (2008), reporting that when irrigated plant sugarcane issues quickly root system, however, there is a deepening as pronounced as observed under rainfed conditions, because the roots tend to concentrate in the more humid soil.…”
Section: Root Areamentioning
confidence: 96%
See 1 more Smart Citation
“…Esta resposta verificada no material mais pobre em P e mais argiloso, não foi evidenciada no PVA, de textura média e com maior disponibilidade inicial do nutriente (Tabela 1 e 2), sugerindo que o método de aplicação assumiria menor importância em solos com elevada disponibilidade de P. Os solos semelhantes ao PVA, com menor fator capacidade, possibilitam melhor aproveitamento do P pelas plantas, quando a água não é fator limitante à produção (Costa et al, 2006;Farias et al, 2008).…”
Section: Figuraunclassified
“…However, it is known that the damage promoted by stress depends on which developmental phase the plant is and the stress duration. The longer the period with low water availability, the greater the damage on stalks and saccharose yield (Inman-Bamber 2004, Farias et al 2008.…”
Section: Abstract Resumomentioning
confidence: 99%